2014
DOI: 10.1097/qai.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Transmitted Drug Resistance of HIV-1 During 2008–2012 Antiretroviral Therapy Scaling up in Southern Vietnam

Abstract: There was no increase in TDR prevalence in Southern Vietnam during and after the 2008-2012 rapid scale up of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Considering this fact and the report from other parts of Vietnam (6.6 ) (17,18,24), our results on the DRM rate in the IDU population (47.4 ) and in the MSM population (33.3 ) are still alarmingly high.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Considering this fact and the report from other parts of Vietnam (6.6 ) (17,18,24), our results on the DRM rate in the IDU population (47.4 ) and in the MSM population (33.3 ) are still alarmingly high.…”
Section: Discussionmentioning
confidence: 48%
“…The DRM rate in the ART naïve HIV-positive population ranges from 2.6 to 5.3 in countries such as China, India, Thailand, Hong Kong, Philippines, and Malaysia. Studies in Vietnam have shown an HIV drug resistance rate of around 3.5 to 8.2 (12,(17)(18)(19)(20). Higher DRM rates, 9.2 and 14.2 , were observed among ART-naïve MSM in Thailand and China, respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug treatment often increases the risk of subsequent transmission of drug resistance in new cases of an HIV infection. The Y181C mutation was also reported in treatment-naive individuals among different cohorts (see Table S1 in the supplemental material) at 2.3% (1/43), 1.1% (1/91), 0.6% (1/156), 3.0% (3/101), and 1.6% (2/129) of treatment-naive subtype C-infected individuals in Mozambique (42), in South India (43), in KwaZulu-Natal Provinces in South Africa (44), in Tanzania (45), and in China (46), respectively, and 0.43% of 1,389 treatment-naive individuals in southern Vietnam, where subtype A/E virus was the most prevalent subtype (47). The Y181C mutation or the Y181C/I mutation was detected in 0.4%, 0.3% (1/303), 0.2% (4/2,655), and 1.8% (6/336) of treatment-naive individuals in northern Poland (48), Brazil (49), Mexico (50), and Hondurans (51), respectively, where subtype B was the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Four principle online resources were used to identify national guidelines: The USAID AIDSTAR-One National Treatment Database for HIV [7], AIDSspace Guideline Repository [8], the WHO Database of National HIV and TB guidelines 2005-2011 [9], and the UNAIDS Global Database of HIV/AIDS guidelines [10]. National guidelines had to fulfill the following criteria: published in English, low-or middle-income setting as determined by World Bank income grouping [11], and published between January 1, 2009 (when WHO first adopted the GRADE process), and December 31, 2013.…”
Section: Data Sourcesmentioning
confidence: 99%